ANALISA PRODUKSI ENERGI PHOTOVOLTAIC SEBAGAI INFRASTRUKTUR PENGISIAN DAYA MOBIL LISTRIK DI KANTOR DPRD MUARO JAMBI - Matalata, Hendi; Wustha Johar, Leily; Yulianto, Didik; Sahputra, Riki; Rizki Aldiansyah, Rioni (Jurnal Teknologi dan Vokasi, 2025)
The automotive sector is very important to achieve net zero global emissions to limit global warming because 65% to 80% of the emissions produced come from exhaust and indirect emissions come from fuel. In 2050, the volume of oil production is expected to fall by 55% and gas by 70% and coal will no longer be produced. For this reason, regional governments, especially Jambi province, can be pioneers in preparing to use electric vehicles, starting with the use of official cars in every government agency. Muaro Jambi Regency (Sengeti) is 30.4 km from Jambi City, where the average government employee lives in Jambi City and uses fossil fuel official cars every day. This is of course a long-term global energy security problem. In this research, data analysis was carried out regarding solar radiation and energy production of Photovoltaic (PV) systems using the Photovoltaic Geographical Information System (PVGIS) web application located at the Muaro Jambi DPRD office where the data was used as charging infrastructure for 1 electric car in one trip. . From the research results, there is potential for Photovoltaic (PV) system energy as infrastructure for charging electric cars and allows for 2 units of electric cars with the same specifications, because there is an average energy per day that is not captured at 5512.2 Wh.